SISTEM INFORMASI PEMESANAN ROTI KALLIS BAKERY MENGGUNAKAN METODE PROTOTYPE - Herdiyansyah; Titin Kristiana (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2023)
The problem with Kallis Bakery is that customers cannot shop online, have not been optimal in providing product information because Kallis Bakery only uses Instagram and Facebook advertising media as promotional media, buying and selling activities are slow and time-consuming, where customers who are interested in buying the desired product must come directly to the store, the bread sales information system at Kallis Bakery is currently running, In order to run even better, it is expected to design and create a web-based bread sales application system. Then it is expected that the Kallis Bakery bread sales application system can be implemented and tested first before running. This method uses the prototype method in building software to improve and make it easier for Kallis Bakery customers to transact with the increasing use of the internet among the community, Kallis Bakery innovates with online shopping, web-based online ordering systems can be done easily with this application, data storage systems in databases, important data can be stored properly. Keywords: Booking, prototype, web-based